Enhanced biophotocurrent generation in living photosynthetic optical resonator - Roxby, Daniel N. (2020)
Bioenergy from photosynthetic living organisms is a potential solution for energy‐harvesting and bioelectricity‐generation issues. With the emerging interest in biophotovoltaics, extracting electricity from photosynthetic organisms remains challenging because of the low electron‐transition rate and photon collection efficiency due to membrane shielding. In this study, the concept of “photosynthetic resonator” to amplify biological nanoelectricity through the confinement of living microalgae (Chlorella sp.) in an optical micro/nanocavity is demonstrated. Strong energy coupling between the Fabry–Perot cavity mode and photosynthetic resonance offers the potential of exploiting optical resonators to amplify photocurrent generation as well as energy harvesting. Biomimetic models and living photosynthesis are explored in which the power is increased by almost 600% and 200%, respectively. Systematic studies of photosystem fluorescence and photocurrent are simultaneously carried out. Finally, an optofluidic‐based photosynthetic device is developed. It is envisaged that the key innovations proposed in this study can provide comprehensive insights in biological‐energy sciences, suggesting a new avenue to amplify electrochemical signals using an optical cavity. Promising applications include photocatalysis, photoelectrochemistry, biofuel devices, and sustainable optoelectronics.